2019
DOI: 10.1080/10942912.2019.1651738
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life of Saurida tumbil during Storage at Refrigeration Condition as affected by Gelatin-Based Edible Coatings Incorporated with propolis Extract

Abstract: The aim of this study was to evaluate the effect of gelatin coating in combination with propolis extract (PE) on the microbiological (total mesophilic bacteria and psychrotrophic count), physicochemical (total volatile basic nitrogen (TVBN), 2-thiobarbituric acid reactive substances (TBARS), and free fatty acid (FFA)), and sensory characteristics in Saurida tumbil fillets during refrigerated storage (4 ± 1°C). The results showed that the gelatin-PE samples reduced the extent of lipid oxidation, as judged by TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
5
6
0
Order By: Relevance
“…Propolis extracts mainly ethanolic ones significantly inhibited the growth of lactic acid bacteria, which is in agreement with result of other studies (Duman & Özpolat, 2015;Tosi, Ré, Ortega, & Cazzoli, 2007). Similar results were described by Nessianpour et al (2019); which they reported that gelatin coating with PE was effective in inhibiting bacterial growth.…”
Section: Microbiological Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…Propolis extracts mainly ethanolic ones significantly inhibited the growth of lactic acid bacteria, which is in agreement with result of other studies (Duman & Özpolat, 2015;Tosi, Ré, Ortega, & Cazzoli, 2007). Similar results were described by Nessianpour et al (2019); which they reported that gelatin coating with PE was effective in inhibiting bacterial growth.…”
Section: Microbiological Analysissupporting
confidence: 91%
“…Gelatin coating with PE was effective in inhibiting bacterial growth (Nessianpour, Khodanazary, & Hosseini, 2019). Similar results were obtained in other study reported by Ebadi, Khodanazary, Hosseini, and Zanguee (2019) who reported that incorporating PE into chitosan solution reduced the extent of lipid oxidation, improved the TVB-N and pH values of the Nemipterus japonicus fillets significantly compared to untreated sample, thus extending the shelf life of N. japonicus fillet approximately >10 days.…”
supporting
confidence: 87%
See 3 more Smart Citations